Persepsi Mahasiswa Terhadap Aplikasi TikTok Sebagai Media Dakwah - Ashabul Kahpi; Emi Puspita Dewi (Social Science and Contemporary Issues Journal, 2024)
The presence of social media such as Tik Tok makes the communication process easier and more effective. This is the case with da'wah activities. Da'wah must be in accordance with the concept of al-Islamu sholih likulli zaman wa makan (in accordance with the conditions of time and era). This research is entitled "Student Perceptions of the TikTok Application as a Da'wah Media". The purpose of this study was to determine student perceptions of the TikTok application as a medium for da'wah. This research uses a qualitative descriptive method. The data collection techniques used are observation, interview, and documentation. Data analysis was carried out through data reduction, namely summarizing the results of interviews, observations, and data analysis. The results of this study indicate that, the perception of MD students views TikTok as a media for da'wah is an effective and relevant media if used in preaching. TikTok is also perceived as a new or innovative preaching media, besides other media. TikTok is also responsive and can meet current needs, because it contains positive things and content, such as information, educational content, comedy, business, and various other positive things.